Superhighway robbery : preventing e-commerce crime - Newman, Graeme R.; Clarke, R. V. G. (Cullompton : Willan, 2003)
This book analyzes the expanding crime opportunities created by the Internet and e-commerce, and it explains how concepts of crime preventi on developed in other contexts can be effectively applied in this new e nvironment. The authors note that the Internet and associated e-commerc e constitute a lawless "wild frontier" where users of the Internet can anonymously exploit and victimize other users without a high risk of be ing detected, arrested, prosecuted, and punished. For acquisitive crimi nals who seek to gain money by stealing it from others, e-commerce thro ugh the Internet enables them to "hack" their way into bank records and transfer funds for their own enrichment. Computer programs that are re adily available for download on the Web can be used to scan the Web for individual computers that are vulnerable to attack. By using the Inter net addresses of other users or using another person's or organization' s computers or computing environment, criminals can hide their trails a nd escape detection. After identifying the multiple opportunities for c rime in the world of e-commerce, the book describes specific steps that can be taken to prevent e-commerce crime at particular points of vulne rability. The authors explain how two aspects of situational crime prev ention can prevent Internet crime. This involves both a targeting of in dividual vulnerabilities and a broad approach that requires partnership s in producing changes and modifications that can reduce or eliminate c riminal opportunities. The authors apply the 16 techniques of situation al crime prevention to the points of vulnerability of the e-commerce sy stem. The points of vulnerability are identified and preventive measure s are proposed. In discussing the broad approach of institutionalized a nd systemic efforts to police e-commerce, the book focuses on ways to i ncrease the risks of detection and sanctions for crime without undue in trusions on the freedom and privacy of legitimate Internet and e-commer ce users.
Foreword / Gloria Laycock -- Preface -- Chap. 1. Situational crime p revention in the information society -- Chap. 2. The e-commerce environ ment -- Chap. 3. E-commerce as the target of crime -- Chap. 4. Informat ion as a hot product -- Chap. 5. Risk analysis of online shopping -- Ch ap. 6. Reducing opportunities for e-commerce crime -- Chap. 7. Policing e-commerce -- Chap. 8. Situational prevention and the 'society of cont rol'.
Includes bibliographical references and index.
Keywords: Internet fraud -- Prevention; Computer crimes -- Prevention